1991
DOI: 10.1161/01.cir.83.6.1999
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular diastolic collapse. An echocardiographic sign of regional cardiac tamponade.

Abstract: We conclude that left ventricular diastolic collapse is a frequent sign of regional cardiac tamponade and could be a useful marker of tamponade in postoperative patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
1
2

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(47 citation statements)
references
References 20 publications
3
41
1
2
Order By: Relevance
“…Hence, selective compression of the left ventricle may be seen in a significant number of cases. This was seen in 4 patients in one study [7], and was also reported by Jones et al [11] and by Chuttani et al [12]. However, selective compression due to loculated effusion can affect the right atrium and venae cavae [3], right ventricular outflow tract [9], left atrium [13], or a combination of one, two, three, or all four chambers [7].…”
Section: Clinical Diagnosissupporting
confidence: 55%
“…Hence, selective compression of the left ventricle may be seen in a significant number of cases. This was seen in 4 patients in one study [7], and was also reported by Jones et al [11] and by Chuttani et al [12]. However, selective compression due to loculated effusion can affect the right atrium and venae cavae [3], right ventricular outflow tract [9], left atrium [13], or a combination of one, two, three, or all four chambers [7].…”
Section: Clinical Diagnosissupporting
confidence: 55%
“…A large eVusion with a circumferential echo space of > 1 cm anteriorly or posteriorly is reported to be a powerful predictor of the development of tamponade. 3 Nevertheless, cardiac tamponade is usually a clinical diagnosis which is confirmed by echocardiography, where right ventricular (or right atrial) collapse is usually observed [4][5][6][7] ; however, left ventricular collapse is also seen, especially in the more advanced stages of tamponade, 8 and following cardiac surgery. 9 Rarely, despite life threatening tamponade, right atrial or right ventricular diastolic collapse may not be present in some patients, particularly following cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…An extreme degree of tamponade can result in compression and collapse of the whole RV chamber. A similar mechanism can be operative in the manifestation of left ventricular diastolic collapse (LVDC), when a loculated effusion adjacent to the LV causes tamponade [16]. similar mechanism.b One or more of these signs (RAC, RVDC, and LAC) may be present in a given patient, and their predictive accuracy varies.…”
Section: Echocardiographic Findingsmentioning
confidence: 99%
“…Because the RV and RA walls are often adherent to the chest wall following cardiac surgery, the most common location of the effusion is posterior [16]. Consequently, the typical right-sided findings such as RAC and RVDC may not be seen.…”
Section: Regional Tamponadementioning
confidence: 99%